Exploring the link between perceptions on corruption levels and the prevalence of high unemployment in South Africa - Molise, Tieho Francis (University of the Witwatersrand, Johannesburg, 2023)
The failure of the government to deliver leads to dissatisfaction and loss of hope amongst the citizens. The focus of this study was to provide a disclosure on the knowledge and insights of how the citizens perceive the Government towards fighting corruption and creating jobs. This single based country study, which adopted a correlational research design, was aimed to investigate whether there is an association between the perceived high corruption levels and ability of the government to create jobs. The study used a Chi-Square test for association which ruled out the Null hypothesis in favour of the Alternative hypothesis that there is a significant (P=0.000) association between the perception of corruption and job creation for both round five and round eight Afrobarometer surveys covered in this study. The study also found that the citizens in South Africa continued to perceive the government to be doing very badly in handling job creation and fighting corruption. Therefore, the Government ought to address the voice of the nation to retain its own reputation, supremacy and for progression of the economy and wellbeing of its nation at large
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management (in the field of Public and Development Sector Monitoring and Evaluation) to the Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2023
Keywords: Perceptions of corruption; Perceptions of job creation; unemployment; Corruption; UCTD; SDG-8: Decent work and economic growth